Pemberdayaan Masyarakat dalam Pemanfaatan Daun Stroberi (Fragaria x ananassa) Sebagai Teh Herbal - Widodo, Tanty Sulistiani; Abdillah, Muhammad Jundi Abdillah; Nopi, Nopi Okta Piani (Ma'soem University, 2025)
Strawberries contribute significantly to the local economy and serve as a major attraction in the development of agrotourism in Sugihmukti Village. In the cultivation process, only the fruit is typically utilized, while other parts such as the leaves are often discarded without optimal use. This condition generates agricultural waste that can negatively impact the environment if not properly managed. Processing strawberry leaves into herbal tea provides a strategic solution that supports product diversification and enhances economic value. The objective of this activity is to improve the knowledge and skills of the Sugihmukti Village community in utilizing strawberry leaves as a health-promoting herbal tea to support local economic independence. This activity applied the Community-Based Participatory Research (CBPR) approach to ensure active community participation. The Focus Group Discussion (FGD) method was used to evaluate participants’ level of understanding. The results showed an increase in community knowledge and skills in utilizing strawberry leaves and unsellable fruits as herbal tea, as evidenced by the improvement in participants’ knowledge scores from 53% (pre-test) to 90.6% (post-test), with an increase of 37.6%, indicating program success. Community enthusiasm, support from local authorities, and collaboration with various institutions serve as a strong foundation for developing the village’s potential flagship products.